2000
DOI: 10.1046/j.1365-2249.2000.01197.x
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine synthesis and cellular inflammatory changes in lungs of mice bearing p40taxof human T-lymphotropic virus type 1

Abstract: SUMMARYTo elucidate the pathogenic mechanisms of human T-lymphotropic virus type 1 (HTLV-1)-associated lung inflammation, we conducted a histopathological and molecular analysis study using transgenic mice bearing pX region of this virus. In these mice, accumulations of inflammatory cells consisting mainly of lymphocytes were present in peribronchiolar and perivascular areas and alveolar septa, while control littermate mice did not show such changes. In situ hybridization showed that the anatomic distribution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
20
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 38 publications
(69 reference statements)
4
20
0
Order By: Relevance
“…The types of chemokines induced in the lungs of MHV-68-infected mice confirm and extend the findings of Sarawar and colleagues (21) and are similar to those seen following infection with other respiratory viruses (7,8,14,32), suggesting a common pattern of innate immune response to viral infections of the lungs. Thus, the early expression of MIP-1␣, MIP-1␤, MIP-2, and MCP-1 may be due to release of chemokines from infected cells and may contribute to the recruitment of inflammatory cells to the site of infection.…”
supporting
confidence: 85%
See 2 more Smart Citations
“…The types of chemokines induced in the lungs of MHV-68-infected mice confirm and extend the findings of Sarawar and colleagues (21) and are similar to those seen following infection with other respiratory viruses (7,8,14,32), suggesting a common pattern of innate immune response to viral infections of the lungs. Thus, the early expression of MIP-1␣, MIP-1␤, MIP-2, and MCP-1 may be due to release of chemokines from infected cells and may contribute to the recruitment of inflammatory cells to the site of infection.…”
supporting
confidence: 85%
“…Infection with respiratory viruses has been associated with lung inflammation and the induction of chemokines critical to the inflammatory response (7,8,10,14,32). Furthermore, induction of chemokine synthesis occurred early after infection in these studies and was postulated to be part of the innate immune response to viral infection.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…It is commonly known that tax activates cellular signaling pathways, and transactivates cellular immune responses, including those leading to cytokine production. We previously reported that there were increased mRNA expression levels of Th1 related cytokines and chemokines in the lungs of transgenic mice bearing the pX region (44), with a significant correlation between the tax mRNA expression levels and pathological inflammatory changes in the lungs of these transgenic mice (45).…”
Section: Discussionmentioning
confidence: 94%
“…We observed induction of CCL5 both at the mRNA and protein levels in JPX-9 cells. Furthermore, Miyazato et al 53 have demonstrated elevated expression levels of CCL5 in lungs of transgenic mice and the correlation between its expression and the severity of histopathological changes in the lung. CCL5 may contribute to the accumulation of T lymphocytes in the lungs, leading to inflammation of the lungs in HTLV-I carrier.…”
Section: Expression Of Ccr5 On Htlv-i-infected T-cell Lines and Infilmentioning
confidence: 99%